A história e a geografia na concepção da disciplina de ciências sociais no ESG1 em Moçambique: subsídios epistemológicos e didáctico-metodológicos para a revisão curricular em curso - Selimane, Remane (2012)
This research fits into the theme of curriculum development. Its focus is to understand the curriculum revision in Mozambique, since the mid 2000s. It seeks to understand to what extent this process has been ongoing on the basis of valid theoretical assumptions and how that has been reflected in the improvement or not of the quality of education offered. It critically analyzes curriculum integration in the area of Social Sciences, in the Junior General Secondary Education. Specifically, the research analyzes the process of creating of the discipline of Social Sciences in the Field of Communication and Social Sciences. Thus, the basic categories are: curriculum (development, reform and integration) and (discipline of) Social Sciences, as well as patriotic references and values. The relevance of this discussion is justified primarily by its timeliness. The study is based on the epistemological principles of dialectic paradigm and the assumptions of qualitative research and develops through documentation, bibliographic and documentary research, questionnaires and interviews. The empirical research was based on documents on the subject issued at the Ministry of Education of Mozambique and fieldwork benefited from the testimony of 20 (twenty) teachers and 10 (ten) national level educational supervisors or tecnitions. In the four chapters of this work, besides the Introduction and Conclusions, it is discussed, in turn, the origin of the research problem, the author's personal motivations for its achievement and other aspects that reinforce the rationale, objectives, methodology and track the results produced. There's, also, an historical critical review on the construction of the curriculum, taking in Mozambique, having as a starting point the time when the author started to be involved in it; a critical analysis of Teaching Programs of History and Geography in the Junior General Secondary Education, and data collected through interviews and questionnaires. A theoretical approach based on the categories enunciated above and supported by critical authors. Outline the conclusions, in conclusions, which sum up the basic ideas of work, seeking to respond to the challenge put at first. The work provides an outline of some alternative strategies to the process of curriculum construction in haste. It has been assumed that the proposed strategies conducive to achieving the aims of the Social Sciences Area at General Secondary Education and strengthen the contribution of this area in the curriculum structure particularly, and in the development of Mozambican General Secondary Education curriculum, in general